Theoretical analysis of current trends of innovative development of pedagogical universities - Пономарьова, Галина Федорівна (Scientific notes of the pedagogical department)
In the paper identified and analyzed urgent directions for managing of innovative development of pedagogical universities.The author notes that such components of the educational system of Ukraine as the content of educational activities, staffing, teaching resources, material and technical base, evaluation and monitoring results should be reformed.